Pediatric Cancer Research using Healthcare Big Data - Hyery Kim (The Korean Society of Pediatric Hematology-Oncology, 2022)
Health insurance big data provides real-world evidence of unmet needs in clinical practice and breakthroughs in the medical industry that will impact the future of health care. Big data is expected to revolutionize the current medical paradigm and usher in an era of personalized medicine. In Korea, the Health Insurance Review and Assessment Service and the National Health Insurance Service established large-capacity healthcare big data open systems in 2011 and 2013, respectively, and are providing researchers with secured healthcare big data. However, concerns have been raised regarding the quality of big data-based research. Thus, numerous obstacles remain in leveraging big data research to change medical practice. This paper describes the understanding and practical applications of healthcare big data in pediatric cancer research, ranging from clinical research design using health insurance big data to medical writing.